Different unilateral force control strategies between athletes and non-athletes - Kim, R. K.; Park, C.; Jeon, K.; Park, K.; Kang, N. (Journal of Biomechanics, 2021)
This study investigated continuous visuomotor tracking capabilities between athletes and non-athlete controls using isometric force control paradigm. Nine female athletes and nine female age-matched controls performed unilateral hand-grip force control tasks with their dominant and non-dominant hands at 10% and 40% of maximal voluntary contraction (MVC), respectively. Three conventional outcome measures on force control capabilities included mean force, force accuracy, and force variability, and we additionally calculated two nonlinear dynamics variables including force regularity using sample entropy and force stability using maximal Lyapunov exponent. Finally, we performed correlation analyses to determine the relationship between nonlinear dynamics variables and conventional measures for each group. The findings indicated that force control capabilities as indicated by three conventional measures were not significantly different between athlete and non-athlete control groups. However, the athletes revealed less force regularity and greater force stability across hand conditions and targeted force levels than those in non-athlete controls. The correlation analyses found that increased force regularity (i.e., less sample entropy values) at 10% of MVC and decreased force regularity (i.e., greater sample entropy values) at 40% of MVC were significantly related to improved force accuracy and variability for the athlete group, and these patterns were not observed in the non-athlete control group. These findings suggested that the athletes may use different adaptive force control strategies as indicated by nonlinear dynamics tools.